PSYCHOLOGICAL AND COGNITIVE ASPECTS OF RAPID LEARNING - Ostapovskyi, Oleksii (SWorldJournal, 2024)
The article is dedicated to studying the psychological and cognitive aspects of rapid learning, including the analysis of effective techniques for optimizing the learning process. The purpose of the research is to identify the main psychological and cogni